Systematic analysis of affordable housing development and pricing structure in Shenzhen, China - Sing, Chun Pong; Love, Peter E. D.; Fung, Wing Hong; He, Yun Zi (International Journal of Strategic Property Management, 2015)
As a result of urban housing reform in China, it has become increasingly difficult for low and middle income families to purchase a house. In response to the growing demand for affordable housing, the Chinese Government has developed a specific housing policy to enable families to purchase properties from the private sector. The pricing mechanism of such housing is completely based on the family affordability and the profit margin of developers. To ensure the provision of housing for low and middle-income families, the future trend of affordable housing prices has become a concern for developers, consumers and may adversely influence the implementation of the current national housing policy. In this paper a systematic analysis of affordable housing development and its pricing structure is undertaken for the city of Shenzhen. As information pertaining to the factors influencing house prices is imperfect, a Grey model, which requires a limited amount of data to reflect unknown behavior, is constructed to provide a forecast for affordable house pricing. The analysis indicates that the government should adjust their current affordable housing policy to accommodate the forecasted upward trend in house prices.First Publish Online: 1 Apr 2015